2003
DOI: 10.1007/s10350-004-6662-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Monitoring of Colorectal Cancer by L6 Blood Serum Polymerase Chain Reaction Is Superior to Carcinoembryonic Antigen-Enzyme-Linked Immunosorbent Assay

Abstract: L6 is more sensitive and precise than carcinoembryonic antigen in diagnosing and monitoring colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
0
14
0
2
Order By: Relevance
“…TM4SF1 is reported to be a prognostic marker in a number of malignant tumors. In lung (14) and colorectal cancer (34) patients, increased expression of TM4SF1 was shown to be significantly associated with early postoperative relapse and shorter survival. In contrast, our study revealed that decreased expression of TM4SF1 was significantly associated with shorter survival and early local spread in PDAC patients, suggesting that TM4SF1 plays an inhibitory role in pancreatic cancer relapse and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…TM4SF1 is reported to be a prognostic marker in a number of malignant tumors. In lung (14) and colorectal cancer (34) patients, increased expression of TM4SF1 was shown to be significantly associated with early postoperative relapse and shorter survival. In contrast, our study revealed that decreased expression of TM4SF1 was significantly associated with shorter survival and early local spread in PDAC patients, suggesting that TM4SF1 plays an inhibitory role in pancreatic cancer relapse and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, the sensitivity and specificity of SEPT-9 were confirmed with 73% and 91%, respectively (12). Guanylyl cyclase C (GCC) RNA (5) and L6 RNA (6) showed high sensitivity with 74% and 79% at 95% and 100% specificity but have not yet been extensively validated.…”
mentioning
confidence: 98%
“…Carcinoembryonic antigen (CEA) and carbohydrate antigens, for example, CA19-9 have been assessed more intensely but with varying results depending on the study design and the study population (4). Recently, nucleic acid-based markers, including RNA, DNA, and epigenetic modifications, have come into focus (5)(6)(7)(8)(9)(10)(11)(12). Although some of the markers, for example, a panel of 5 RNA markers (7) or hypomethylated SEPT-9 DNA (11), showed good sensitivities of 88% and 68%, the respective specificities of 69% and 89% will burden a high number of patients with a false-positive result if used for screening.…”
mentioning
confidence: 99%
“…These Francisco, CA)]. TM4SF1 is also being evaluated as a diagnostic marker for colorectal and gastric cancers and as a target for therapy with monoclonal antibodies (90,91).…”
Section: And the References Therein)mentioning
confidence: 99%